Drafting the Substance Materials of The Regional Regulation of Badung Regency on Public Service - Astariyani, Ni Luh Gede; Nurmawati, Made (Udayana Journal of Social Sciences and Humanities; Vol 1 No 1 (2017): UJoSSH, Feburary 2017DO - 10.24843/UJoSSH.2017.v01.i01.p08, 2017)
The Government of Badung Regency provides public services, both in the forms of services and goods, to its community as part of its duty in performing governance. In the implementation, such public services are regulated in regulation which is derived from the existence of policy in the delegation of authority. The regional regulation as such is containing what so called the substance materials. The substance materials of Regency/City Regional Regulation mean that such regulation contains typical substance materials that are not contained in other Laws and Regulation both in the local and central level. The formulations of legal norms in the Regional Regulation are conducted by using the single and pairs formulations. The targets that will be realized, the scope of regulation and drafting direction of Regional of Badung Regency on Public Services, among others: scope of public services, integrated service system, guidelines for the standrad services preparation, the proportion of community groups and categories in a tiered services and community participation in performing the service.